Bacteriophage therapy: an alternative to antibiotics in the age of multi-drug resistance - Rajeshwar Reddy Kasarla; Rahul Reddy Kasarla; Sruthi Reddy Thummala; Laxmi Pathak (Janaki Medical College Journal of Medical Science, 2024)
Phage therapy involves the use of specific viruses that can infect and lyse pathogenic bacteria. Since, antibiotic resistance is widely increasing among bacteria phages offer a promising field as natural, self-replicating and self-limiting antibiotics. Clinical trials are conducted to use phages against multi-drug resistant bacterial infections. The most powerful and cost-effective application of phage therapy is in the treatment of diseases such as cholera and dysentery. While phage therapy has been around for over 100 years, the treatment still is not a main part of medicine. Phage therapy has largely existed on the fringes of medicine, particularly in Western countries like the USA, where it is occasionally approved for compassionate use, on emergency basis when no other approved therapies are available. This review was undertaken to discuss, review and highlight the importance and future research of phage therapy.